Metallosis Following Titanium Implant Use in the Hand: A Case Report and Review of Current Literature - Tang, Camelia Qian Ying; Chuah, Khoon Leong; Teoh, Lam Chuan (Journal of Hand and Microsurgery, 2022)
Adverse reaction to metal debris (ARMD) consists of a spectrum of changes ranging from pure metallosis to aseptic lymphocytic vasculitis-associated lesion and granulomatous inflammation. Currently described ARMD cases are mainly limited to arthroplasty, typically total hip and knee arthroplasties in the lower limb and total wrist arthroplasty in the upper limb. Hypersensitivity to a metallic implant in fracture fixation is rare, and a severe form of metallosis has not been reported so far. In this paper, we present a case of ARMD occurring 10 years after the use of titanium implants for fracture fixation in the hand. Intra-operative findings, histopathological results, and a literature review on ARMD are also described.
Keywords: Metallosis; adverse reaction to metal debris; titanium implants; fracture fixation; Metacarpal base fractures